Practical considerations for coaching athletes with learning disabilities and neurodevelopmental disorders - Thurston, R. J.; Alexander, D. M.; Michaud, M. (International Sport Coaching Journal, 2022)
Learning disabilities and neurodevelopmental disorders are the most prevalent disabilities that affect learning. This paper will provide practical recommendations and observations for coaching athletes with three common learning disabilities (dyslexia, dysgraphia, and dyscalculia) and two neurodevelopmental disorders (attention deficit hyperactivity disorder and autism spectrum disorder). Adapted from the literature and in conjunction with previous experiences, the authors provided a range of recommendations for coaches to consider implementing within their practices. The recommendations place an emphasis on the knowledge, strategies, and behaviors of the coach and their role in providing an inclusive, safe, and accessible space for athletes—with or without disabilities—rather than problematizing the disability or the person. Coaches are encouraged to consider their coaching environment (i.e., structure, physical elements, equipment), communication styles (i.e., language, delivery, feedback), and behaviors (e.g., frequent check-ins, review of material). Furthermore, coaches are encouraged to critically reflect on their preconceived biases, assumptions, and experiences with disability and how these play a role in influencing their coaching practices.Considering the prevalence of people with learning disabilities or neurodevelopmental disorders, it is essential for coaches to have access to disability-specific information while remaining cognizant of the needs of the individual when providing an inclusive environment for all.